Peran Disiplin Kerja, Emotional Intelligence, dan Happiness At Work dalam Mencapai Kinerja Karyawan yang Optimal - Khoirun Nisa, Fahma; Rahmawati, Fitri Maulidah (CV. ITTC INDONESIA, 2025)
Employee performance is a key factor in determining the success and achievement of organizational goals. However, various challenges such as low work discipline, poor emotional intelligence management, and declining happiness at work pose obstacles to achieving optimal performance. This study investigates the role of work discipline, emotional intelligence, and workplace happiness in achieving optimal employee performance at the Yogyakarta Technical Education Training Center (BLPT). The research aims to test the influence of work discipline, emotional intelligence, and workplace happiness on optimal employee performance. The study employs a quantitative method using non-probability sampling techniques, specifically a census/total sampling approach. The population consisted of all BLPT Yogyakarta employees, with 75 respondents. The research instrument was a questionnaire distributed offline via hard copies. Data analysis was conducted using multiple linear regression analysis through IBM SPSS version 25. The research results indicate that: (1) Work discipline has a negative and insignificant effect on employee performance, (2) Emotional intelligence has a positive and significant effect on employee performance, (3) Happiness at work has a positive and significant effect on employee performance. The conclusion is that work discipline has a negative and insignificant effect on employee performance, as it has become a basic standard possessed by employees, thus not creating significant performance variations among employees. Conversely, emotional intelligence and happiness at work have a positive and significant effect on employee performance, indicating that these two variables are important factors in improving employee performance in that environment.